EVALUASI KEMAMPUAN KOGNITIF IPAS SISWA SEKOLAH DASAR MATERI TATA SURYA MELALUI PENILAIAN OTENTIK PROYEK - Ari Nur Kristanti; Yuni Pantiwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of project-based authentic assessment in improving students’ conceptual understanding and skills in the topic of the Solar System. The assessment was conducted on 11 student groups who developed planetary arrangement media as part of science learning. The results indicate that this approach had a positive impact on students' cognitive abilities, particularly in understanding factual concepts and applying them in real-life contexts. The average scores across five assessment aspects were as follows: conceptual understanding (80), group performance (80), product (78), portfolio (80), and presentation skills (76). These scores reflect that the majority of students met the success criteria within the “good” category. The use of authentic assessment allowed students not only to comprehend the material but also to develop critical thinking, collaboration, and self-reflection skills. Observations during the project implementation showed that students were highly enthusiastic, actively engaged in group discussions, and eager to design and build the solar system models. In-depth interviews also revealed that students found it easier to understand the material through project-based methods compared to conventional methods such as lectures or textbook reading. Authentic assessment has proven to effectively integrate cognitive, affective, and psychomotor domains, offering a meaningful learning experience that is contextualized to real-world situations. Therefore, this approach is suitable for implementation as a science learning strategy in elementary and secondary education.